The Villainous Pontianak? Examining Gender, Culture and Power in Malaysian Horror Films - Lee, Yuen Beng (Penerbit Universiti Putra Malaysia, 2016)
The pontianak is widely recognised as the most dreaded supernatural being in Malay folklore and mythology. Often described as a fearsome mythical creature with vampire-like qualities, she is said to have fangs, possesses ghost-like traits and can only be subdued using a sharp object which is usually a nail struck to the back of her neck. She is also recognised through her high-pitched shrieks, long flowing hair and a fondness for the blood of children. Despite possessing such fearsome and horrifying characteristics, the pontianak peculiarly remains popular among Malaysians as the horror film genre has always been popular among Malaysian and Asian audiences due to its deep roots in religious and superstitious beliefs. Many Asian nations have shared cultural, historical and social characteristics. Cross cultural influences across borders are common in shaping each other’s culture and a number of Malaysian horror films have been influenced by the Noh and Kabuki-influenced ‘shunen’ (revenge) and ‘kaidan’ (ghost mystery) stories. While the horror film is in fact a commercial venture, the genre is also filled with socio-cultural and political contestations. As such, these narratives reflect certain socio-cultural and political anxieties of given moments within the location of the film’s production. This paper therefore examines the pan-Asian cultural influences in the current wave of Malaysian horror. As the pontianak is also always female, this paper then examines how the employment of female monstrosity articulate male fears around female empowerment and suggests a broader challenge to a sense of normality, cultural and religious beliefs